Comparison of Bristow procedure and Bankart arthroscopic method as the treatment of recurrent shoulder instability - Abolghasem Zarezade; Mohammad Dehghani; Ali Reza Rozati; Hossein Saeid Banadaki; Neda Shekarchizade (Advanced Biomedical Research, 2014)
Background: Anterior shoulder dislocation is the most common major joint dislocation. In patients with recurrent shoulder dislocation, surgical intervention is necessary. In this study, two methods of treatment, Bankart arthroscopic method and open Bristow procedure, were compared. Materials and Methods: This clinical trial survey had been done in the orthopedic department of Alzahra and Kashani hospitals of Isfahan during 2008-2011. Patients with recurrent anterior shoulder dislocation who were candidates for surgical treatment were randomly divided into two groups, one treated by Bankart arthroscopic technique and the other treated by Bristow method. All the patients were assessed after the surgery using the criteria of ROWE, CONSTANT, UCLA, and ASES. Data were analyzed by SPSS software. Results: Six patients (16.22%) had inappropriate condition with ROWE score (score less than 75); of them, one had been treated with Bristow and five with Bankart (5.26 vs. 27.78). Nine patients (24.32%) had appropriate condition, which included six from Bristow group and three treated by Bankart technique (31.58 vs. 16.67). Finally, 22 patients (59.46%) showed great improvement with this score, which included 12 from Bristow and 10 from Bankart groups (63.16 vs. 55.56). According to Fisher′s exact test, there were no significant differences between the two groups (P = 0.15). Conclusion: The two mentioned techniques did not differ significantly, although some parameters such as level of performance, pain intensity, use of analgesics, and range of internal rotation showed more improvement in Bristow procedure. Therefore, if there is no contraindication for Bristow procedure, it is preferred to use this method.